Targeting solid tumor cells with novel photosensitive ruthenium-based metal-organic compounds. (c2016) - Farhat, Stephanie Roy (2016)
Cancer incidence has been increasing worldwide in the last few decades. Solid tumors are hard to treat, primarily due to drug resistance as well as to the struggle in delivering the drugs specifically to the tumor. Various therapeutic approaches for treating solid tumors have been exploited. A very promising approach has been the use of Ruthenium-based complexes conjugated to different ligands that are characterized by having a photochemical potential rendering them only active after exposure to light, which can be ultimately specifically delivered to the site of tumor. This study aims to find the most efficient Ru-based compounds on a set of 6 cell lines from different solid tumors. Different ruthenium precursors (bis-bidentate), final complexes (tris-bidentate) and free phenanthroline- or bipyridine-derived ligands were tested. The bis-bidentate complexes tested were four: Ru-I: [Ru(II)(1,10-phenanthroline)2Cl2]; Ru-II: [Ru(II)(4,7-diphenyl-1,10-phenanthroline)2Cl2]; Ru-III: [Ru(II)(4,7-diphenyl-1,10-phenanthroline-disulfonate)2Na2]2+ and Ru-IV: [Ru(II)(2,2'-bipyridine)2Cl2], along with their corresponding free ligands L-I, L-II, L-III and L-IV, respectively. Ru-II showed significant potency on most of the cell lines tested (5 out of 6), as well as Ru-I on two of them while the others were inert. As for the free ligands, L-II presented major cytotoxic effect on five out of six cell lines, L-I on two cell lines, L-IV on one cell line only. The addition of diphenyl groups to the phenanthroline of L-I rendered its structure bulkier and more hydrophobic (L-II), and showed an increase in its potent activity, same result when it was bound to the metal. Therefore, a structure activity relationship was established between precursors and their free ligands. However, when adding sulfonate groups to the diphenylphenanthroline structures, the cytotoxic effect is inhibited in the free ligand and its precursor, L-III and Ru-III respectively, thus suggesting a possible DNA intercalation mechanism of these compounds. On the other hand, neither bipyridine nor its corresponding precursor L-IV and Ru-IV, bipyridine and its corresponding precursor respectively, shown no cytotoxic activity. In addition, four final compounds were synthesized to study the photochemical potential of our metal-based complexes. There structure bear combinations of L-II and L-III yielding the tris-bidentate compounds, Ru-II3, Ru-II2-III, Ru-II-III2 and Ru-III3, having different net charges ranging between +2 and -4, and their effect was studied in the dark and after exposure to blue light. Activity was detected only in Ru-II3 against all the tested cell lines in the dark, Ru-II2-III in three cell lines while the others showed no effect. When exposed to blue light against the astrocytoma cell line all four compounds showed high levels of potency, including Ru-II-III2 and Ru-III3 that were biologically inert in the dark. It is hypothesized that these final compounds’ cytotoxic action is due to the generation of Reactive Oxygen Species (ROS), causing DNA damage, oxidation of amino acids and enzyme co-factors, as well as lipid peroxidation, thus leading to cell death. The ultimate goal is to base future selective anticancer treatments using Ru-based compounds. The mechanisms by which Ru-based compounds work is still being explored, and other ligands and combination of ligands are also being tested to find the most selective, and potent complex.